0\; ,\\\\sin\beta =\sqrt{1-cos^2\beta }=\sqrt{1-\frac{1}{4}}=\frac{\sqrt3}{2}" alt="1)\; \; sin\frac{5\pi }{4}=cos\frac{5\pi }{4}=-\frac{\sqrt2}{2}\; \; ,\; \; tg\frac{5\pi }{4}=ctg\frac{5\pi }{4}=1\\\\sin(-900^\circ)=0\; ,\; \; cos(-900^\circ )=-1\; ,\; \; tg(-900^\circ )=0\; ,\\ctg(-900^\circ )\; -\; ne\; syshestvyet\\\\2)\; \; cosa=-\frac{\sqrt2}{2}\; \; ,\; \; a\in (\pi ,\frac{3\pi}{2})\; \to \; sina<0\; ,\\\\sina=-\sqrt{1-cos^2a}=-\sqrt{1-\frac{2}{4}}=-\frac{\sqrt2}{2}\\\\cos\beta=\frac{1}{2}\; \; ,\; \; \beta \in (0,\frac{\pi}{2})\; \to \; sin\beta >0\; ,\\\\sin\beta =\sqrt{1-cos^2\beta }=\sqrt{1-\frac{1}{4}}=\frac{\sqrt3}{2}" align="absmiddle" class="latex-formula">
![cos(a+\beta )=cosa\cdot cos\beta -sina\cdot sin\beta =-\frac{\sqrt2}{2}\cdot \frac{1}{2}+\frac{\sqrt2}{2}\cdot \frac{\sqrt3}{2}=\frac{\sqrt6-\sqrt2}{4}\\\\3)\; a)\; 1-2sin^2\frac{\pi}{8}=cos(2\cdot \frac{\pi}{8})=cos\frac{\pi}{4}=\frac{\sqrt2}{2}\\\\b)\; \; sin105^\circ =sin(60^\circ +45^\circ )=sin60^\circ \cdot cos45^\circ +cos60^\circ \cdot sin45^\circ =\\\\=\frac{\sqrt3}{2}\cdot \frac{\sqrt2}{2}+\frac{1}{2}\cdot \frac{\sqrt2}{2}=\frac{\sqrt6+\sqrt2}{4}\\\\c)\; \; ctg\frac{7\pi}{4}=ctg(2\pi -\frac{\pi }{4}=ctg(-\frac{\pi}{4})=-ctg\frac{\pi}{4}=-\frac{\sqrt2}{2} cos(a+\beta )=cosa\cdot cos\beta -sina\cdot sin\beta =-\frac{\sqrt2}{2}\cdot \frac{1}{2}+\frac{\sqrt2}{2}\cdot \frac{\sqrt3}{2}=\frac{\sqrt6-\sqrt2}{4}\\\\3)\; a)\; 1-2sin^2\frac{\pi}{8}=cos(2\cdot \frac{\pi}{8})=cos\frac{\pi}{4}=\frac{\sqrt2}{2}\\\\b)\; \; sin105^\circ =sin(60^\circ +45^\circ )=sin60^\circ \cdot cos45^\circ +cos60^\circ \cdot sin45^\circ =\\\\=\frac{\sqrt3}{2}\cdot \frac{\sqrt2}{2}+\frac{1}{2}\cdot \frac{\sqrt2}{2}=\frac{\sqrt6+\sqrt2}{4}\\\\c)\; \; ctg\frac{7\pi}{4}=ctg(2\pi -\frac{\pi }{4}=ctg(-\frac{\pi}{4})=-ctg\frac{\pi}{4}=-\frac{\sqrt2}{2}](https://tex.z-dn.net/?f=cos%28a%2B%5Cbeta%20%29%3Dcosa%5Ccdot%20cos%5Cbeta%20-sina%5Ccdot%20sin%5Cbeta%20%3D-%5Cfrac%7B%5Csqrt2%7D%7B2%7D%5Ccdot%20%5Cfrac%7B1%7D%7B2%7D%2B%5Cfrac%7B%5Csqrt2%7D%7B2%7D%5Ccdot%20%5Cfrac%7B%5Csqrt3%7D%7B2%7D%3D%5Cfrac%7B%5Csqrt6-%5Csqrt2%7D%7B4%7D%5C%5C%5C%5C3%29%5C%3B%20a%29%5C%3B%201-2sin%5E2%5Cfrac%7B%5Cpi%7D%7B8%7D%3Dcos%282%5Ccdot%20%5Cfrac%7B%5Cpi%7D%7B8%7D%29%3Dcos%5Cfrac%7B%5Cpi%7D%7B4%7D%3D%5Cfrac%7B%5Csqrt2%7D%7B2%7D%5C%5C%5C%5Cb%29%5C%3B%20%5C%3B%20sin105%5E%5Ccirc%20%3Dsin%2860%5E%5Ccirc%20%2B45%5E%5Ccirc%20%29%3Dsin60%5E%5Ccirc%20%5Ccdot%20cos45%5E%5Ccirc%20%2Bcos60%5E%5Ccirc%20%5Ccdot%20sin45%5E%5Ccirc%20%3D%5C%5C%5C%5C%3D%5Cfrac%7B%5Csqrt3%7D%7B2%7D%5Ccdot%20%5Cfrac%7B%5Csqrt2%7D%7B2%7D%2B%5Cfrac%7B1%7D%7B2%7D%5Ccdot%20%5Cfrac%7B%5Csqrt2%7D%7B2%7D%3D%5Cfrac%7B%5Csqrt6%2B%5Csqrt2%7D%7B4%7D%5C%5C%5C%5Cc%29%5C%3B%20%5C%3B%20ctg%5Cfrac%7B7%5Cpi%7D%7B4%7D%3Dctg%282%5Cpi%20-%5Cfrac%7B%5Cpi%20%7D%7B4%7D%3Dctg%28-%5Cfrac%7B%5Cpi%7D%7B4%7D%29%3D-ctg%5Cfrac%7B%5Cpi%7D%7B4%7D%3D-%5Cfrac%7B%5Csqrt2%7D%7B2%7D)
![4)\; \; cos^4a+sin^4a-2cos^2a\, sin^2a=(cos^2a-sin^2a)^2=(cos2a)^2=cos^22a\; ;\\\\(1-cos^2a)\cdot ctga=sin^2a\cdot \frac{cosa}{sina}=sina\cdot cosa 4)\; \; cos^4a+sin^4a-2cos^2a\, sin^2a=(cos^2a-sin^2a)^2=(cos2a)^2=cos^22a\; ;\\\\(1-cos^2a)\cdot ctga=sin^2a\cdot \frac{cosa}{sina}=sina\cdot cosa](https://tex.z-dn.net/?f=4%29%5C%3B%20%5C%3B%20cos%5E4a%2Bsin%5E4a-2cos%5E2a%5C%2C%20sin%5E2a%3D%28cos%5E2a-sin%5E2a%29%5E2%3D%28cos2a%29%5E2%3Dcos%5E22a%5C%3B%20%3B%5C%5C%5C%5C%281-cos%5E2a%29%5Ccdot%20ctga%3Dsin%5E2a%5Ccdot%20%5Cfrac%7Bcosa%7D%7Bsina%7D%3Dsina%5Ccdot%20cosa)